Assessing the effect of different shapes of glyco-gold nanoparticles on bacterial adhesion and infections. Issue 86 (11th September 2015) - Chaudhary, Preeti Madhukar; Sangabathuni, Sivakoti; Murthy, Raghavendra Vasudeva; Paul, Ajay; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra
Abstract : Different shapes of glyco gold nanoparticles (AuNPs) tune the bacterial aggregations, which can effectively inhibit the bacterial infection of cells. Abstract : Achieving selective and sensitive carbohydrate–protein interactions (CPIs) using nanotechnology is an intriguing area of research. Here we demonstrate that the different shapes of gold nanoparticles (AuNPs) functionalized with monosaccharides tune the bacterial aggregations. The mechanism of aggregation revealed that the large number of surface interactions of rod shaped mannose-AuNPs with E. coli ORN 178 compared with spherical and star-shaped AuNPs exhibited higher avidity and sensitivity. Moreover, such sensitive binding can be used for effective inhibition of bacterial infection of cells.